Dietary Planning Research Based on Enumeration and Simulated Annealing Algorithms - Zhang, Ke; Jiang, Han; Huang, Qi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the development of society and the improvement of living standards, people are paying more and more attention to healthy eating, especially among college students. Scientifically designing daily recipes which is used to solve the problem of nutritional imbalance when balancing economic benefits has become an important research topic. This study evaluates and adjusts the dietary recipes of male and female college students. The study establishs optimization models with the goals of maximizing protein and amino acid scores, minimizing meal costs, and the both. It also quantifies the values, scores, and meal costs of each protein and amino acid, and constructs a goal programming model with daily energy and nutrient intake as constraints. Based on the principle of balanced dietary recipe optimization design, it constructs an optimization model for goal programming, and uses the enumeration method to solve the problem, construct a 0-1 vector ti, and use Matlab to solve for the typical value ti. It further uses simulated annealing algorithm to enumerate in this numerical direction to obtain the results, and evaluates the dietary nutrition of the daily diet.